(untitled) (Scientific journal of the Fergana State University, 2024)
The development of self-educational skills in students has become an increasingly important aspect of modern education. These skills empower students to take responsibility for their own learning, foster a lifelong love for knowledge acquisition, and equip them with the ability to adapt to an ever-changing world. However, despite the recognized significance of self-educational skills, numerous challenges persist in their effective cultivation. The purpose of the article is to identify and explore the key problems associated with developing self-educational skills among students. It begins by highlighting the limited emphasis placed on self-directed learning within traditional education systems, wherein the focus often remains on teacher-centered instruction and standardized testing. The lack of opportunities for students to explore their own interests, set learning goals, and engage in independent inquiry contributes to a significant barrier in the development of self-educational skills. The article discusses the role of technology in both facilitating and hindering self-directed learning. While digital resources and online platforms offer vast opportunities for independent exploration and knowledge acquisition, they also present distractions and challenges in managing time effectively. The article emphasizes the need for educators to harness the potential of technology while providing guidance on its responsible usage